Connotative-Evaluative Transformations of Adjective ‘Patriotic’: Linguistic Embodiment of Concept PATRIOTISM in Russian - N. V. Radbil (Научный диалог, 2023)
The value components of the concept PATRIOTISM are studied. The immediate focus of the proposed research is the connotativeevaluative transformations of the adjective ‘patriotic’ in representative contexts. The technique of discursive corpus analysis was used. The material for the study is the lexicographic interpretations of the word ‘patriotic’, presented in a number of Russian explanatory dictionaries, as well as the language data of the Russian National Corpus. It is shown that the implicit positive appraisal for the word ‘patriotic’ is naturally generated by its general language semantics ʽimbued with patriotism, filled with patriotismʼ, ʽexpressing a feeling of patriotismʼ, etc., as a result of which positive-evaluative connotations ʽhaving value significance for the speakerʼ are implied; ʽcorresponding to national ideals and valuesʼ; ʽtrue, correct, the one that should beʼ. The analyzed material confirmed the relevance for the speech implementation of the word ‘patriotic’ models of negative evaluation in the usage of overly affected patriotism; external, ostentatious patriotism; false, imaginary, false patriotism; insufficient patriotism. The conclusion is made about the complexity of the ethnos “language of values” structure, about the ambiguity of certain phenomena linguistic evaluation of reality mechanisms in the speech practices of native speakers.